2004
DOI: 10.1111/j.1745-4530.2004.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Variable Diffusion of Sodium During Debittering of Green Olives

Abstract: Time-variable average effective diffusion coefficients of sodium in the skin and flesh were determined using Macroscopic Mass Balances from experimental data obtained during debittering of green olives, variety Arauco at temperatures of 15, 20 and 25C and lye concentrations of 1.50, 2.25 and 3.00% of NaOH. The effective diffusion coefficient of sodium increased with treatment time at both surfaces of the skin, while it varied very little within the flesh, and in many cases, remained almost constant during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…and Maldonado and Zuritz (2004a) computed effective diffusion coefficients of sodium during the debittering of green olives varieties Arauco and Aloreña. Zuritz and Maldonado (2004) quantified the diffusion of sodium through olive skins during and after treatment with NaOH, while Maldonado and Zuritz (2004b) evaluated the diffusion phenomena considering variable diffusion coefficients. In both cases they observed an increase in the skin diffusion coefficient with treatment time.…”
Section: Introductionmentioning
confidence: 99%
“…and Maldonado and Zuritz (2004a) computed effective diffusion coefficients of sodium during the debittering of green olives varieties Arauco and Aloreña. Zuritz and Maldonado (2004) quantified the diffusion of sodium through olive skins during and after treatment with NaOH, while Maldonado and Zuritz (2004b) evaluated the diffusion phenomena considering variable diffusion coefficients. In both cases they observed an increase in the skin diffusion coefficient with treatment time.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidations were performed either by autoxidation at alkaline pH values where the oxidation rate is high [5] in the presence of NaOH (which is used for debittering of olives [23] at pH 9.0) or by a commercial polyphenol oxidase (tyrosinase), which can mimic the action of the polyphenoloxidase present in olives and olive oil [12].…”
Section: G a L L E Y P R O O Fmentioning
confidence: 99%
“…In the 2018/2019 season, the average weight (5.57 ± 0.18 g) and flesh/stone ratio (6:1) of the olives indicated that the penetration of the alkali into the fruits would be medium high. In addition, according to the fat content (15%–16%, data provided by the manufacturer) it was assumed that the free fatty acids present inside the fruits could neutralize part of the alkali (Maldonado & Zuritz, 2004). On the other hand, the moderate content of total sugars in the pulp (19.17 ± 0.31 g/kg of pulp) indicated that the alkaline and washing treatments should not be either intensive or long, since they would reduce a large part of the fermentable matter.…”
Section: Resultsmentioning
confidence: 99%